“I Must Cite Some Examples of Their Full Capacity for Expression”: Thoughts toward the History of Ethnomusicology (Revista Argentina de Musicología, 2023)
In this article Philip V. Bohman reviews the history of the approaches to so-called exotic musical cultures that gave birth to ethnomusicology. Reviewing the literature from the earliest descriptions of the music of the Other at the dawn of modernity, Bohlman discusses the forms of representation of what he calls an incipient ethnomusicology and asks how those descriptions gained more and more a scientific dimension in the discipline. Without downplaying the colonialist or Eurocentric implications of early ethnomusicological practices, Bohlman invites us to delineate, through a critical reading of the discipline’s past, the elements that should nurture our practices when we investigate or transmit the music of other cultures in current times.
Keywords: Ethnomusicology; history of ethnomusicology; colonialism; reflexivity